Effect of graphite and MoS2 based solid lubricants for application at wheel-rail interface on the wear mechanism and surface morphology of hypereutectoid rails. (May 2021) - Fasihi, Panahsadat; Kendall, Olivia; Abrahams, Ralph; Mutton, Peter; Lai, Quan; Qiu, Cong; Yan, Wenyi
Abstract: The effectiveness of two graphite-based and one MoS2 -based solid lubricants subjected to high creepages were experimentally assessed. This research correlated the evolution of coefficient of traction (CoT) to in-depth wear surface morphology and microstructure. The lubricating potential of these solid lubricants to reduce wear and thereby extend the operation life of rail components was comprehensively evaluated. The graphite-based lubricants were able to reduce the CoT and improve the wear resistance considerably. Furthermore, the graphite-based lubricant with lower carbon content was found to be effective at all tested conditions, offering 30%–55% reduction in CoTs, longer retentivity, and better surface morphology. However, the MoS2 -based lubricant did not offer significant reduction in the CoT and resulted in substantial abrasive wear at higher creepages. Highlights: Tribological properties of three solid lubricants were experimentally studied. A modified experimental procedure suitable for a typical twin-disc is established. Retentivity performance is correlated to wear mechanisms. MoS2 SL resulted in significant abrasive wear and gouging of the roller surfaces. Graphite SLs were more effective in reducing wear of pre-existing surface damage.